Cause-Effect Analysis on the Wheat Market in Poland - Anna SZCZEPANSKA-PRZEKOTA (Communications of International Proceedings, 2021)
The research aim focus on determining the cause and effect relationship on the wheat market in Poland. Based on the observation of prices, purchase volumes, exports and imports in Poland, futures contracts from the Matif exchange, an attempt was made to establish the position of the Polish wheat market in the world and the relationship between agricultural producers and purchasing companies. Modeling was carried out on the basis of correlation tests, causality as well as cause and effect linear and power models. It was established that the wheat market in Poland is strongly shaped by the world market, Poland turns out to be the recipient of world prices. In addition, the paper proves that the position of Polish agricultural producers in relation to purchasing enterprises is weak, they receive lower purchase prices than the world ones. Most of the relations are in line with expectations, in particular the negative correlation between prices and purchase volume, but it was also found that trade balance did not affect the prices on the Polish market. Thus, agricultural producers' fears that imports harm the market are unfounded. Lower prices in Poland stimulate exports.
Keywords: Wheat market; prices; purchase; trade balance; cause-effect analysis.